Anterior cruciate ligament rupture: Management, prapaedeutics and diagnosis (Research, Society and Development, 2024)
Introduction: One of the factors that contribute to knee stabilization and its function is the Anterior Cruciate Ligament (ACL), which prevents anterior displacement, internal rotation of the tibia, and hyperextension. ACL rupture is one of the most common injuries. Objective: To understand the mechanisms, diagnostic tools, and therapeutic strategies. Methodology: The study consists of a literature review conducted in four stages: identification of the topic and selection of the guiding research question; establishment of inclusion and exclusion criteria for studies and literature search; evaluation of the studies included in the narrative review; and interpretation and presentation of the review. As inclusion criteria, the search was limited to articles written in English and Portuguese, published between 2018 and 2024. Discussion: For the diagnosis of ACL rupture, clinical history and physical examination must be correlated, and if necessary, complementary imaging tests should be conducted. After the diagnosis, the treatment aims to restore knee functionality, prevent future injuries and osteoarthritis, and optimize the patient's quality of life. Thus, there are three main treatment options: 1) rehabilitation as the first line followed by ligament reconstruction (ACL-R); 2) ACL-R and postoperative rehabilitation; and 3) preoperative rehabilitation, ACL-R, and postoperative rehabilitation. Patients across all modalities show significant improvements in knee function and quality of life. Final considerations: The choice of treatment must be personalized, aiming not only at physical recovery but also at the patient's quality of life and preferences.